RESPONSIBILITY OF INFLUENCERS WHO CONDUCT STOCK POMMS AS A LAW ENFORCEMENT MEASURE FOR INVESTORS - Agatha Edelweiss; Joanne Emmanuel; Ricky Siregar (Universitas Labuhanbatu, 2024)
Many stock investment influencers often engage in stock pumping and dumping on social media.